Advancements in Automatic Seed Sowing Machines: A Comprehensive Review and Analysis - Ajayi, Segun; Adedeji, Audrey (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
The most crucial step in farming is sowing. It is a labourintensive process that takes a long time and a lot of human work. Here, we suggest creating a completely automated seed-planting robot to complete this operation. Four motors are used by the suggested robot to move it in the required direction. We deposit seeds into a little bracket. The robot has a funnel-like setup that allows seeds to be poured into the lower container. To take up a small amount, we employ a shaft with gears shaped like bucket teeth.The robot’s front is made up of a bent plate that drags on the ground to create a slot before seeds are placed inside it. The robot’s back is made out of a bent rod that resembles a tail and is used to cover sown seeds with dirt by pouring soil on top of them.As a result, the system used a cleverly constructed mechanical robotic system to fully automate the seed sowing operation